2013
DOI: 10.3897/zookeys.319.4340
|View full text |Cite
|
Sign up to set email alerts
|

New data on aphid fauna (Hemiptera, Aphididae) in Algeria

Abstract: A survey of aphids was carried out during the period 2008-2011 in different regions of Algeria by collecting and identifying aphids and their host plants. Aphids were collected from 46 host plants. Forty-six species were reported including thirty-six species which were recorded for the first time in this country and thirty species which were recorded for the first time in the Maghreb (North Africa). This study extends the number of known Algerian aphid to 156 species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Hodjat, 1981 Global Distribution: Iran (Hodjat, 1981), in Iraq Daoud and El-Haidari (1968) recorded this species feed on Euphrates poplar at Baghdad province during April and July. Koch, 1854(= Chaitophorus versicolor Koch, 1854 Global Distribution: Widely distributed in Europe (Pintera, 1987;Blackman and Eastop, 2015); North Africa (Boukhris-Bouhachem et al, 2007;Laamari et al, 2013); Asia including Kazakhstan, Mongolia, East Siberia (Pashchenko, 1988); North and South America (Rubín de Celis and Ortiz, 1992;Ramirez et al, 2004); in Iraq Daoud and El-Haidari (1968) and Al-Ali (1977) recorded this species on Populus euphratica in Baghdad at August; Diyala and Baquba at October.…”
Section: Commentsmentioning
confidence: 99%
“…Hodjat, 1981 Global Distribution: Iran (Hodjat, 1981), in Iraq Daoud and El-Haidari (1968) recorded this species feed on Euphrates poplar at Baghdad province during April and July. Koch, 1854(= Chaitophorus versicolor Koch, 1854 Global Distribution: Widely distributed in Europe (Pintera, 1987;Blackman and Eastop, 2015); North Africa (Boukhris-Bouhachem et al, 2007;Laamari et al, 2013); Asia including Kazakhstan, Mongolia, East Siberia (Pashchenko, 1988); North and South America (Rubín de Celis and Ortiz, 1992;Ramirez et al, 2004); in Iraq Daoud and El-Haidari (1968) and Al-Ali (1977) recorded this species on Populus euphratica in Baghdad at August; Diyala and Baquba at October.…”
Section: Commentsmentioning
confidence: 99%
“…According to Blackman & Eastop (), eight aphid species can live on Cupressus spp. Until now, no aphid species had been found on these cypress trees in Algeria (Laamari et al ., , ). In Tunisia, Boukhris‐Bouhachem et al .…”
Section: Introductionmentioning
confidence: 97%
“…According to Blackman & Eastop (1994), eight aphid species can live on Cupressus spp. Until now, no aphid species had been found on these cypress trees in Algeria (Laamari et al, 2010(Laamari et al, , 2013. In Tunisia, Boukhris- Bouhachem et al (2007) and Ben Halima-Kamel (2012) have reported the presence of the arborvitae aphid Cinara thujafilina Del Guercio and the cupressus aphid Cinara cupressi (Buckton) on Cupressus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Aphids belonging to this subfamily are characterized by a specialization on Coniferae of the families Pinaceae and Cupressaceae (Delfino & Binazzi, 2000). In Algeria, the genus Cinara is represented by five species: Cinara cedri (Mimeur), Cinara juniperi (de Geer), Cinara escherichi (B€ orner), Cinara laportei (Remaudi ere) and Cinara pini (Linnaeus) (Laamari et al, 2010(Laamari et al, , 2013. The latter was first found in Algeria in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Laamari et al . (, ) reported its first observation on Pinus halepensis Miller from the region of Biskra, in the south‐east of Algeria. A survey of aphids and their parasitoids in Algiers led to the first finding of C. pini in the capital and also the first record for Algeria of Pauesia silana Tremblay, 1969 which was found in mummies of C. pini .…”
Section: Introductionmentioning
confidence: 99%